2019
DOI: 10.1016/j.thromres.2019.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent activity-based probe for the selective detection of Factor VII activating protease (FSAP) in human plasma

Abstract: The zymogen form of circulating Factor VII activating protease (FSAP) is activated by histones that are released as a consequence of tissue damage or excessive inflammation. This is likely to have consequences in a number of disease conditions such as stroke, atherosclerosis, liver fibrosis, thrombosis and cancer. To investigate the existence, as well as the concentration, of active FSAP (FSAPa) in complex biological systems an active site probe is needed. We used Hybrid Combinatorial Substrate Library (HyCoSu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The results obtained with the SPD-isoforms in this study largely match the earlier observations made with plasma-derived proteins 9,27 as well as proteins obtained from mammalian expression system 7,18 . During the course of the preparation of this manuscript we have been able to develop a novel substrate, an active-site probe as well as a specific and selective inhibitor for FSAP 29 . Similarly, we also found that this preparation of FSAP can recapitulate the effects of plasma FSAP on gene expression in cells 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained with the SPD-isoforms in this study largely match the earlier observations made with plasma-derived proteins 9,27 as well as proteins obtained from mammalian expression system 7,18 . During the course of the preparation of this manuscript we have been able to develop a novel substrate, an active-site probe as well as a specific and selective inhibitor for FSAP 29 . Similarly, we also found that this preparation of FSAP can recapitulate the effects of plasma FSAP on gene expression in cells 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Effect of NNKC9/41 on mouse plasma: Mouse FSAP differs in fours amino acids (29)(30)(31)(32)(33) from human FSAP in the MA-FSAP-38C7 binding sequence in the NTR (Fig. 3C).…”
Section: Effect Of Nnkc9/41 On Hemostasismentioning
confidence: 99%
“…Rut et al obtained a synthetic FSAP substrate by means of a HyCoSuL with arginine fixed in P1 position and 19 natural and 108 unnatural amino acids in P2-P4 position. ACC was used as fluorophore [66]. Excitation was conducted at 320 nm and the emission was measured at 460 nm.…”
Section: Coumarin Substrates For Serine Proteasesmentioning
confidence: 99%
“…The probe was assembled through the introduction of the linker-connected biotin or Cy5 substructure at the N-terminus of the peptide. A nucleophilic attack of the active-site serine at the warhead's phosphorous leads to irreversible inhibition and labeling of the target protease [66]. This prototypical stepwise approach towards an ABP starting from the identification of a preferred amino acid sequence has frequently been demonstrated.…”
Section: Coumarin Substrates For Serine Proteasesmentioning
confidence: 99%
See 1 more Smart Citation